In Vitro Study of Pseudomonas spp. Isolated from Soil - Jaya Tripathi1, Preeti Tiwari2*, Swati Rosh Ekka1 and (Journal of Phytology, 2011)
Pseudomonas spp., a soil microorganism, associated in the rhizosphere zones of crop fields are powerful phosphate solubilizers. The principal mechanism for mineral phosphate solubilization is the production of organic acids, and acid phosphatases that play a major role in the mineralization of organic phosphorous in soil. (RodrÃƒÂguez, H. and Fraga, R. 2000). Thus, Pseudomonas are eco-friendly and bring about solubilization of bound phosphates in soil with out any environmental hazard. This experiment was conducted to isolate soil Pseudomonas spp. from different agrobased areas of Korea district of C.G. and study its behavior taking different parameters.Ã‚Â From 25 soil samples collected, bacterial cultures were isolated and four were identified as Pseudomonas spp. and further studied their cultural and microscopic characteristics in vitro.